Isolation and characterization of Staphylococcus aureus from raw cow milk in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2014)
NOTE: On 05/01/2015, Marzia Rahman was added to the website as the second author of this paper. This author was already on the PDF of the article.The study was intended for identification and characterization of Staphylococcus aureus isolated from raw cow milk. A total of 47 milk samples were collected from Sheshmore, Shutiakhali and Bangladesh Agricultural University Dairy Farm, Mymensingh. Using bacteriological, biochemical and PCR-based identification schemes, 12 (25.53%) isolates were confirmed as S. aureus. All the isolates showed ?-hemolysis on 5% sheep blood agar. S. aureus specific nuc gene (target size 279-bp) was amplified in the cases of all isolates. The isolates were found as resistant to Penicillin (100%), Erythromycin (75%) and Amoxicillin (100%). On the other hand, the isolates were sensitive to Ciprofloxacin (83.33%), Oxacillin (100%), Cloxacillin (100%) and Neomycin (100%). The isolated S. aureus showed increased resistance to broad spectrum antibiotic (e.g., Ciprofloxacin). As many people have a tendency to drink raw milk and raw milk products, there is high risk of S. aureus infection in human. DOI: http://dx.doi.org/10.5455/javar.2015.b47